Narrowing the climate information usability gap - Lemos, Maria Carmen; Kirchhoff, Christine J.; Ramprasad, Vijay (Nature Climate Change, 2012)
Climate-change-related risks pose serious threats to the management of a wide range of social, economic and ecological systems. Managing the se risks requires knowledge-intensive adaptive management and policy-m aking actively informed by scientific knowledge, especially climate sc ience1. However, potentially useful climate information often goes unu sed1,2. This suggests a gap between what scientists understand as usef ul information and what users recognize as usable in their decision-ma king. We propose a dynamic conceptual model to address this gap and hi ghlight strategies to move information from useful to usable to reduce climate-related risks.